Genetically determined blood pressure, antihypertensive drug classes, and frailty: A Mendelian randomization study - Zhuang, Z; Li, Y; Zhao, Y; Huang, N; Wang, W; Xiao, W; Du, J; Dong, X; Song, Z; Jia, J; Liu, Z; Clarke, R; et al. (Wiley Open Access, 2024)
Observational studies have suggested that the use of antihypertensive drugs was associated with the risk of frailty; however, these findings may be biased by confounding and reverse causality. This study aimed to explore the effect of genetically predicted lifelong lowering blood pressure (BP) through different antihypertensive medications on frailty. One‐sample Mendelian randomization (MR) and summary data‐based MR (SMR) were applied. We utilized two kinds of genetic instruments to proxy the antihypertensive medications, including genetic variants within or nearby drugs target genes associated with systolic/diastolic BP, and expression level of the corresponding gene. Among 298,618 UK Biobank participants, one‐sample MR analysis observed that genetically proxied BB use (relative risk ratios, 0.76; 95% CI, 0.65–0.90; p = 0.001) and CCB use (0.83; 0.72–0.95; p = 0.007), equivalent to a 10‐mm Hg reduction in systolic BP, was significantly associated with lower risk of pre‐frailty. In addition, although not statistically significant, the effect directions of systolic BP through ACEi variants (0.72; 0.39–1.33; p = 0.296) or thiazides variants (0.74; 0.53–1.03; p = 0.072) on pre‐frailty were also protective. Similar results were obtained in analyses for diastolic BP. SMR of expression in artery showed that decreased expression level of KCNH2, a target gene of BBs, was associated with lower frailty index (beta −0.02, p = 2.87 × 10−4). This MR analysis found evidence that the use of BBs and CCBs was potentially associated with reduced frailty risk in the general population, and identified KCNH2 as a promising target for further clinical trials to prevent manifestations of frailty.